Komunikasi Pemasaran CV Laktatridia Dalam Memasarkan Susu Kambing (Studi Kasus Komunikasi Pemasaran dalam Mengenalkan dan Meningkatkan Penjualan Susu Kambing di CV Laktatridia Ciwidey, Bandung) - Iis Saidah (KOM & REALITAS SOSIAL, 2011)
This research uses case study metode wich would give such as comprehensive description of all marketing communication of the CV Laktatridia, complete with its implementation and problems that they are facing in doing the marketing of the goats milk.The research decides that the main target objective of the marketing Laktatridia product which is developed under the name "ETTA" is the people who understands, care, and middle up class. Laktatridia sells the goat milk using oral and write communication, through advertising, personal selling, direct marketing and trade expo. The media uses by CV Laktatridia are face to face communication, telephone, brochure, banner, website, and expo which information about goat milk brand, name and address of the company, and the quality of the product. Laktatridia develops fresh goat milk in cup with original taste.The marketing communication division "ETTA" goat milk has a lots of barrier such as they didn't have marketing professional employee and less general employee, Gaot milk is less familiar on the public, and less awareness of the public about the benefit of milk. The model of marketing communication which is developed by Laktatridia has six steps communication processes; they are evaluate the objective, stake message communication content, selecting the right channel, generate credidble sources,Â  and eliminating the flaws design.The conclusion of the research decides marketing communication which is developed by Laktatridia less effective, need to optimalization and new innovation in doing marketing communication to more effective in the future.The suggestions of the research are Laktatridia need to access information of goat milk more large reach, recruit professional employee, compromy with supermarket or distributor, strive for stable organization structure and doing development product with innovatif method so it will be easy in marketing and increase of audience interest to goat milk.